NEW ANTIFRICTION SILUMIN AK15M3 - V. Ju. Stetsenko; A. I. Rivkin (Литьë и металлургия)
It is shown that billets out of antifrictional silumin AK15M3, obtained by iterative casting in stationary crystallizer with j t system of cooling, surpass in frictional wear resistance similar ones out of antifrictional aluminium bronze and can be used as its substitute in friction units.